Impact of Cyber Security in Different Application of E-Governance: Securing Networked Systems in E-Governance (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cyber security refers to the ability to control access to networked systems and the information they contain. Where cyber security controls are effective, cyberspace is considered a reliable and trustable digital infrastructure. The area where cyber security access controls are incomplete, absent and not designed properly then this is considered as the wild west of the digital age. Even those who work in the security profession will have a different view of cyber security depending on the aspects of cyberspace with which they personally interact. Whether a system is a physical facility or a collection of cyberspace components, the role of a security professional assigned to that system is to plan for potential attack and prepare for its consequences.